PEMAKNAAN MAHASISWA TERHADAP KONTEN PRANK KDRT PADA KANAL YOUTUBE BAIM PAULA - Hadinda Maharani Sekar Putri; Nawiroh Vera (Universitas Baturaja, 2023)
The study examined student exorbitations on youtube's content of domestic violence made by baim wong and Paula verhoeven. The domestic violence prank video narrated the domestic abuse report to the old kebayoran police. The theories used are the theories of reception analysis of Stuart hall (encoding-decoding) that have three types, the dominant positions of hegemonic, negotiation and opposition. The purpose of this research is to describe the growing noble university student's conception of domestic violence prank content in the baim Paula youtube channel. The data-gathering technique USES in-depth interviews with ten informers who are active students of the creative communications and design faculty, the budi university. The results of burial with 50 answers of the informant, there were 13 dominant exorcists, 15 negotiation empties and 22 elimination of opposition. It's the research. The results of outusing the use of opposition to domestic violence prank content that went viral in social media was much richer than the informants. With the violent prank video in the home, the informant thinks it could change people's view of the police image. Nevertheless, the informant says there are many other ways to create educational content on domestic violence that is more informative.